RESILIENSI PADA REMAJA PUTRI YANG MENGALAMI KEHAMILAN TIDAK DIINGINKAN AKIBAT KEKERASAN SEKSUAL - Disa Dwi Fajrina (Journal of Research and Measurement in Psychology, 2017)
ABSTRACT This study aims to provide an overview of resilience in teenagers girl who experience unwanted pregnancy due to sexual abuse. The approach used in this study is a qualitative approach with a qualitative case study approach. Data collection techniques used were interviews, observation and documentation. Data were analyzed using qualitative data analysis techniques and techniques of data validity checks using triangulation.These results indicate that both the resilience so that the subject has the ability to positively adapt to the event of unwanted pregnancy due to sexual abuse. Subject I adapt to calm down and think over the matter while subject II adapting to talk to someone nearby. Both subjects also have a seventh aspect of building resilience with the capability of different quality. The subject I is better to regulate and control the negative impulse that is felt while subject II more visible sense of optimism and efficacy of the problem itself. The results also showed that support from the nearest such as family, friends, is one of the most influential factor on the development of resilience both subjects. Keywords: Resilience, teenagers girl, unwanted pregnancy, sexual abuse